Hamilton rating scale for depression-24 (HAM-D24) as a novel predictor for diabetic microvascular complications in type 2 diabetes mellitus patients. (December 2017) - Pan, Shuo; Liu, Zhong-Wei; Shi, Shuang; Ma, Xun; Song, Wen-Qian; Guan, Gong-Chang; Zhang, Yong; Zhu, Shun-Ming; Liu, Fu-Qiang; Liu, Bo; Tang, Zhi-Guo; Wang, Jun-Kui; et al.
Abstract: The study was designed to investigate whether the hamilton rating scale for depression (24-items) (HAM-D24 ) can be used to predict the diabetic microvascular complications in type 2 diabetes mellitus (T2DM) patients. 288 hospitalized patients with T2DM were enrolled. Their diabetic microvascular complications including diabetic nephropathy, diabetic retinopathy, diabetic peripheral neuropathy and diabetic foot as well as demographic, clinical data, blood samples and echocardiography were documented. All the enrolled patients received HAM-D24 evaluation. The HAM-D24 score and incidence of depression in T2DM patients with each diabetic microvascular complication were significantly higher than those in T2DM patients without each diabetic microvascular complication. After the adjustment of use of insulin and hypoglycemic drug, duration of T2DM, mean platelet volume, creatinine, albumin, fasting glucose, glycosylated hemoglobin type A1C, left ventricular ejection fraction, respectively, HAM-D24 score was still significantly associated with diabetic microvascular complications ( OR = 1.188–1.281, all P < 0.001). The AUC of HAM-D24 score for the prediction of diabetic microvascular complication was 0.832 (0.761–0.902). 15 points of HAM-D24 score was considered as the optimal cutoff with the sensitivity of 0.778 and specificity of 0.785. In summary, HAM-D24 score may be used as a novel predictor of diabetic microvascular complications in T2DM patients. Highlights: HAM-D24 scores could be used to predict the diabetic microvascular complication in T2DM patients (AUC of 0.832 (0.761–0.902). 15 points of HAM-D24 score was the optimal cutoff for the prediction of diabetic microvascular complications in T2DM patients (sensitivity of 0.778 and specificity of 0.785). HAM-D24 score was significantly associated with diabetic microvascular complications after adjustments ( OR = 1.188–1.281, all P < 0.001).